Baboons' hand preference resists to spatial factors for a communicative gesture but not for a simple manipulative action. Issue 6 (12th July 2013) - Bourjade, Marie; Meunier, Hélène; Blois‐Heulin, Catherine; Vauclair, Jacques
ABSTRACT Olive baboons (Papio anubis) do acquire and use intentional requesting gestures in experimental contexts. Individual's hand preference for these gestures is consistent with that observed for typical communicative gestures, but not for manipulative actions. Here, we examine whether the strength of hand preference may also be a good marker of hemispheric specialization for communicative gestures, hence differing from the strength of hand preference for manipulative actions. We compared the consistency of individuals' hand preference with regard to the variation in space of either (i) a communicative partner or (ii) a food item to grasp using a controlled set‐up. We report more consistent hand preference for communicative gestures than for grasping actions. Established hand preference in the midline was stronger for gesturing than for grasping and allowed to predict the consistency of hand preference across positions. We found no significant relation between the direction of hand preference and the task. © 2013 Wiley Periodicals, Inc. Dev Psychobiol 55: 651–661, 2013.